Found in (survey) translation: lessons learned while engaging with a wharekura in Southland, New Zealand. (2nd January 2018) - Ward, Aimee L.; Wyeth, Emma H.; McGee, Rob; Freeman, Claire; Cameron, Claire
ABSTRACT: We liaised with a wharekura (Māori language immersion school) to translate and disseminate an online survey for a group of Māori youth in Southland, New Zealand (NZ). The focus of this article is not results, but the processes of respondent orientation and engagement to more genuinely include Māori in a youth survey. An online survey about transport and well-being was conducted with older teenagers from 12 schools, including the wharekura. After working with wharekura staff and students, the survey was translated from English into te reo Māori using best-practice methods. Steps were taken to safeguard authentic engagement, including how the survey translation was conducted, and how the survey data were shared. This NZ-specific experience adds to the literature about the practice of applying the principle of respondent orientation to the process of translating an existing survey into te reo Māori, demonstrating commitment to some Treaty of Waitangi principles. While this is not a kaupapa Māori research project, it is informed by some kaupapa Māori principles. This may be seen as a limitation of this work; however, we believe there are many positive experiences and lessons to be learned from our approach.